Determinants of dividend payout policy: An empirical study of banking sector of Pakistan - Ahmad , Ishtiaq; Muqaddas, Muhammad Fahid (Applied Studies in Agribusiness and Commerce, 2016)
One good way to communicate financial performance of a bank to its shareholders is the payment of dividend. The present study is attempted to explore the influence of financial efficiency, safety, risk and profitability on dividend policy using panel data of 10 commercial banks listed at Pakistan Stock Exchange (PSX) for a period of 9 years between 2006 to 2014. The panel regression technique is used to analyze the data. The analysis shows a positive relationship of dividend payout ratio with safety and profitability in banking sector of Pakistan. The study identifies a negative association of dividend payout measure with financial efficiency and risk. The results show the statistically significant association of safety, risk and profitability with dividend payout ratio. Based on these findings it is concluded that safety, risk and profitability measures are relatively strong measures for defining dividend policy. The results are strongly indicating that safer the banks, the greater payout ratio the bank has. Moreover; banks with higher profitability and lower non-performing loans (NPLs) are believed to pay more dividends. JEL code: G21, G23, G35